Simulation and experimental study of gas exchange processes in internal 93 combustion engines - L. V. Plotnikov; B. P. Zhilkin; Y. M. Brodov (Известия высших учебных заведений: Проблемы энергетики)
The results of mathematical modeling and experimental studies of the gas exchange processes in the intake and exhaust tracts piston engines with supercharging and without him was presented in the article. Modeling on the basis of software Diesel-RK, developed in the MSTU named after N. Bauman was made in the work. Experimental studies were conducted on full-scale models of the single-cylinder engine. The calculated and experimental dependences of change of the instantaneous velocity and pressure of the gas flow in the gas paths from the crank angle were presented in the article. The comparison of the results of the studies are summarized. It was found that the most reliable results of numerical simulation are in periods of open valves.